Extraction and Characterization of Natural Fiber from Stem of Cardiospermum Halicababum. Issue 6 (3rd June 2021) - Vinod, A; Vijay, R; Singaravelu, D. Lenin; Sanjay, M R; Siengchin, Suchart; Yagnaraj, Y; Khan, Shakeel
ABSTRACT: The current study deals with the investigation on the properties of lignocellulose fiber from the stem of Cardiospermum Halicababum. The Cardiospermum Halicababum fibers (CHF) were extracted from its stem by manual retting process. The retted fibers were analyzed for various physical, chemical, crystalline, thermal stability, tensile and morphological properties as per standard procedure. From the chemical investigation, it was found that the CHF has cellulose (59.82%), hemicellulose (16.75%), lignin (9.3%) and wax (1.3%). The CHF possessed a crystallinity index of 32.21%, with thermal stability up to 336°C. The average ultimate tensile strength of CHF was 20.7 ± 1.0 MPa. Morphological characteristics showed lesser lacuna space in between the cell walls thereby preventing the reduction in strength properties.